Clean Water Act environmental compliance program review of ten air force bases and water quality survey - Hoeffner, Jacob, author; Carlson, Kenneth, advisor; Carter, Ellison, committee member; Didier, John, committee member (Colorado State University. Libraries, 2024)
This study includes two main components. First, environmental compliance program reviews (ECPRs) of ten AF bases investigated the permits, programs, and compliance records at an installation level. Due to the depth of the ECPRs, detailed performance metrics from EPA ECHO, EASIER, and OSD databases were integrated into the ECPRs findings. Second, a survey further investigated trends identified in the ECPRs across 25 participating installations. The relevant performance metrics were used to evaluate the effectiveness of water programs that participated in the survey. Systemic compliance risks in permit management, data management, and stormwater and wastewater infrastructure were identified.
Keywords: NPDES; stormwater; Clean Water Act; wastewater; regulatory compliance